2021
DOI: 10.3390/ani11092554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Thermal Stress on Performance, Energy Metabolism, Antioxidant Activity, Brain Serotonin, and Blood Biochemical Indices of Broiler Chickens

Abstract: The aim of this paper was to investigate the effects of chronic thermal stress on the performance, energy metabolism, liver CoQ10, brain serotonin, and blood parameters of broiler chickens. In total, 100 one-day-old chicks were divided into two equal groups of five replicates. At 22 days of age and thereafter, the first group (TN) was maintained at a thermoneutral condition (23 ± 1 °C), while the second group (TS) was subjected to 8 h of thermal stress (34 °C). The heat-stressed group showed significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
4
8
0
Order By: Relevance
“…HS further reduced GPx and GR while SOD was unaffected. The decreased antioxidant enzymes observed in this study confirmed the claim from multiple studies ( Ahmed-Farid et al, 2021 , Song et al, 2018 ; Hu et al, 2021 ; Wang et al, 2021 ) that HS can induce oxidative stress by disrupting the redox status ( Wang et al, 2021 ). The antioxidant capacity and radical scavenging activity of seaweed are positively correlated with flavonoid concentration and the presence of flavonoids can be influenced by seaweed geographical area, harvest time, period of collection and extraction methods ( Cotas et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…HS further reduced GPx and GR while SOD was unaffected. The decreased antioxidant enzymes observed in this study confirmed the claim from multiple studies ( Ahmed-Farid et al, 2021 , Song et al, 2018 ; Hu et al, 2021 ; Wang et al, 2021 ) that HS can induce oxidative stress by disrupting the redox status ( Wang et al, 2021 ). The antioxidant capacity and radical scavenging activity of seaweed are positively correlated with flavonoid concentration and the presence of flavonoids can be influenced by seaweed geographical area, harvest time, period of collection and extraction methods ( Cotas et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Heat stress ( HS ) is a significant problem in modern poultry production ( Ahmed-Farid et al, 2021 , Calik et al, 2022 , Huang et al, 2015 , Liu et al, 2020a , Quinteiro-Filho et al, 2010 , Zhang et al, 2017 ), causing considerable economic losses, which are conjected to surge in coming years with the rise of global temperature ( Abdel-Moneim et al, 2021 ). Current poultry genotypes experience a fast growth rate, which reduces their tolerance to heat, leading to various metabolic disorders in chickens ( Varasteh et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…From day 22 to 24, all the chickens from the two groups were raised with the same temperature and humidity settings (24 °C and 60% relative humidity). Next, from day 25 to 29, the HS group was exposed to 33 °C (with 60% relative humidity) for eight hours each day [ 37 , 38 ]. However, the chickens from the Ctl group were maintained at 24 °C of temperature and 60% of relative humidity during the whole experiment (day 25 to 29).…”
Section: Methodsmentioning
confidence: 99%
“…Their feathers work as thermal insulation, preventing heat dissipation, and their body parts that are not covered by feathers are in a smaller proportion. In this regard, when they encounter thermal stress, broilers reduce their feed intake and physical activities to minimize metabolic heat production, compromising body weight gain and overall broiler production performance [ 4 , 5 , 6 , 7 , 8 , 9 ]. Recent studies unraveled the events of disturbed metabolic homeostasis, altered antioxidant capacity and hormonal system and impaired gut integrity in the broilers exposed to experimental thermal stress condition [ 2 , 4 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, when they encounter thermal stress, broilers reduce their feed intake and physical activities to minimize metabolic heat production, compromising body weight gain and overall broiler production performance [ 4 , 5 , 6 , 7 , 8 , 9 ]. Recent studies unraveled the events of disturbed metabolic homeostasis, altered antioxidant capacity and hormonal system and impaired gut integrity in the broilers exposed to experimental thermal stress condition [ 2 , 4 , 8 , 9 ]. In addition, properties of the meat, in terms of chemical composition, pH, water-holding capacity and texture, were deviated when the animals were exposed to heat stress [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%